ECONOMIC BASE AREAS FOR RICE PRODUCTION IN WEST JAVA PROVINCE - Samantha, Yuliana (Jurnal Hexagro, 2026)
Achieving self-sufficiency in rice has been pursued in recent years. This study aims to identify the spatial distribution of rice production areas across West Java Province's districts and municipalities. An analysis employs annual rice production data for West Java from 2018 to 2025. The primary analytical tool used in this research is the Location Quotient (LQ). LQ results indicate that the economic base for rice production is predominantly concentrated in the districts of Bogor, Sukabumi, Cianjur, Bandung, Garut, Tasikmalaya, Ciamis, Cirebon, Majalengka, Sumedang, Indramayu, Subang, Karawang, and Bekasi. These findings reinforce the relevance of economic base theory, which posits that sectors with comparative advantages (LQ > 1) serve as a key driver of regional economic growth. In West Java, the food crop subsector — particularly rice — continues to serve as a major engine of rural economic activity, generating multiplier effects across sectors such as trade, transportation, and agro-processing. As a result, these areas can be classified as economic base regions that play a pivotal role in meeting national rice demand and potentially contributing to international markets Keywords: Crop; food; subsector